Brand and generic medications: are they interchangeable? - Al-Jazairi AS; Blhareth S; Eqtefan IS; Al-Suwayeh SA; Al-Jazairi, Abdulrazaq S; Bhareth, Sakra; Eqtefan, Iyad S; Al-Suwayeh, Saleh A (Annals of Saudi Medicine)
Background and Objectives: Generic substitution has become a common practice since the late 1970s in the United States. At that time, many of these generics caused bioavailability problems, which fueled suspicions about their efficacy and safety, and the Food and Drug Administration (FDA) standards for bioequivalence. In Saudi Arabia, the increasing number of local products raised several concerns with regard to switching from brands to generics. Our objective was to review and examine the basis of the controversy surrounding brand and generic interchangeability and to explore a practical approach in pursuing a switch.Data Sources: Articles indexed initially under terms such as generic medications, generic substitution, bioequivalence and bioinequivalence were identified. These terms were used to search the indexing service, MEDLINE (1966-2006). References from the extracted articles, and additional data sources, including the Code of Federal Regulations and Regulatory Guidance from the FDA Center for Drug Evaluation and Research were also reviewed.Data Synthesis: For most drugs, bioequivalence testing generally should enable clinicians to routinely substitute generic for innovator products. However, for narrow therapeutic, critical dose drugs, or for highly variable drugs, safe switching between products cannot be assured. These drugs need special precautions and blood level monitoring upon switching. FDA firmly believes that approved generic and brand drugs can be dispensed with the full expectation that the consumer will receive the same clinical benefit.Conclusion: Performing the switch process is an advisable practice to reduce health care costs in countries with strong post-marketing surveillance program, but caution is to be exercised when narrow therapeutic index drugs or highly variable drugs are prescribed.